The impact of the implementation of social policy on the welfare of capital assistance recipients in Brunei Darussalam - Abdullah, Rose; Zainudin, Mohamad Zahir; Zaini, Muhammad Zaki (Inderscience Publishers, 2023)
This article aims to understand the implementation of social policy in Brunei Darussalam, explore the implementation of social policies on capital assistance recipients, and study the impact of social policy on social development planning in Brunei Darussalam. Data collection is done through face-to-face interview processes, focus groups, observations, document analysis and organisational reports. The main findings of this article are as follows. First, the budget allocation for social welfare is increasing every year. Second, economic investment strategies have changed participants’ living conditions but less attention was given to social investment strategies. Third, a need to strengthen capital assistance and extend this method by providing launch grants to non-governmental organisations so that more targeted groups can be reached. The findings of this article contribute to the improvement of social policy to create a better social welfare ecosystem.